Robert's Dictionary of Industrial Relations / Revised Edition - Roberts Harold S (The Bureau Of National Affairs, Inc, 1971)
Foreword to the Second Edition, Introduction, Guide to Users, Dictionary of Industrial Relations, General Source References.